2002
DOI: 10.1111/j.1530-0277.2002.tb02567.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Apolipoprotein and Lipoprotein Profile After Alcohol Withdrawal: Effect of Apolipoprotein E Polymorphism

Abstract: Alcohol abstinence causes major changes in the antiatherogenic Apos and Lps and may increase those known to be atherogenic. Heavy alcohol consumption seems to alter the effect of apoE polymorphism on apoB levels, and further investigations are needed to clarify the mechanisms involved in this phenomenon: a defect in sialylation of apoE, formation of acetaldehyde adducts on apoB, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Therefore hypertriglyceridemia by any cause appears to be a risk factor for the onset and progression of hepatic damage. Our study shows an association between hypertriglyceridemia and the onset of alcoholic cirrhosis, as well as a contribution of triglycerides by themselves in the early onset of the disease and confirms the interaction of APOE polymorphism and alcohol as reported by Gueguen et al. (2002).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore hypertriglyceridemia by any cause appears to be a risk factor for the onset and progression of hepatic damage. Our study shows an association between hypertriglyceridemia and the onset of alcoholic cirrhosis, as well as a contribution of triglycerides by themselves in the early onset of the disease and confirms the interaction of APOE polymorphism and alcohol as reported by Gueguen et al. (2002).…”
Section: Discussionsupporting
confidence: 91%
“…The higher apo B levels among ɛ4 carriers have been described previously (30), as have the effects of the ɛ polymorphism and alcohol consumption on apo B levels (38). In this study, a significant interaction between alcohol consumption and apo E alleles was found; apo B levels increased considerably as a function of alcohol consumption in ɛ2 but not in ɛ4 carriers, whereas the increase of apo B levels in ɛ3 carriers was relatively modest.…”
Section: Discussionmentioning
confidence: 53%
“…An explanation for this may be that we could obtain only recent self‐reported alcohol consumption data while the suicide attempt in some cases dated back years. Alcohol withdrawal has been proposed as a factor potentially increasing the risk for suicide (Bradvik and Berglund, 2003) and may have an influence on serum lipids although respective reports are equivocal (Huang et al, 1992; Gueguen et al, 2002). In our study, no withdrawal symptoms scale was applied.…”
Section: Discussionmentioning
confidence: 99%